(untitled) (Balneo and PRM Research Journal, 2024)
Background: The main aim of this study was to compare conventional radiograph and computer tomograph (CT)-scan measurements of femoral offset. The second aim was the compare the pre- and postoperative values of femoral offsets as well as the variations cre-ated by total hip arthroplasty (THA) replacements using the same protocol of analysis for a patient operated on both hips by the same surgeon using a modified lateral approach. Methods: The CT protocol involves 1mm slices from top of the iliac crest to the isthmus of the femur, 2mm slices from top to the bottom of femoral condyles and top and bottom of the ankle joint. The CT protocol involves 1mm slices from top of the iliac crest to the isth-mus of the femur, 2mm slices from top to the bottom of femoral condyles and top and bot-tom of the ankle joint. The implant came with an operative plan to guide the neck osteot-omy site, and with its own bone compacting or bone removing rasp according to the in-tramedullary cortical or cancellous bony architecture indicated by the 3D-CTplan. Results: In addition to a clinical review and oxford hip scoring, the patient had postoperative radi-ographs and were reviewed regularly at 6 weeks and 6 months. Conclusions: We conclud-ed that this 3D-CT guided custom design femoral stem produces reliable proximal ‘fit and fill’ and primary stability with restoration of limb length discrepancy with complex prox-imal femoral deformity without the need of a corrective osteotomy. Keywords: hip arthrosis; custom hip prosthesis; rehabilitation